TalkingMats as a decision aid to promote involvement in choice and decision-making around home care services for older people with mild to moderate dementia – study protocol for a randomized controlled trial - Anna Dunér; Angela Bångsbo; Tina M. Olsson (BMC Geriatrics, 2023)
Abstract Background In Sweden, 72% of people with dementia live in ordinary housing. Of these, 50% receive home care services. Older people with dementia may benefit from developments in decision-making support which aim to facilitate their ability to communicate their personal needs and preferences with care managers and staff in home care services. In this study, we will test and evaluate the use of TalkingMats in Swedish municipal home care services for older people with mild to moderate dementia. TalkingMats is a low-technology communication tool, to help people with communication difficulties express their views. It uses a simple system of picture symbols which are placed on a textured mat. This study will provide insight into the extent to which TalkingMats benefits older people with dementia to feel more involved in decisions related to home care services. In addition, this study will assess the extent to which the use of TalkingMats promotes service providers’ efforts to involve service recipients in decision making. The implementation of TalkingMats in home care services will also be studied. Methods A parallel group, two-armed randomized controlled trial design in which TalkingMats and Usual Conversation Method will be compared. Two specific situations where older people with dementia must make decisions about home care services will be studied. First, a follow-up needs-assessment conversation between study participants and care managers will be studied. Second, a conversation between participants and home care staff regarding the delivery of the decided home care services will be studied. In addition, a qualitative approach will be used to gain an understanding of study participant and service provider experiences of the impact and implementation of TalkingMats. Discussion The combined exploratory, descriptive, and experimental study design is considered an important strength which will facilitate multi-facetted knowledge production concerning the involvement and communication needs of older people with dementia generally and within the context of home care services specifically. Combining qualitative and quantitative methods will maximize our ability to assess the effects of TalkingMats. Trial registration ClinicalTrials.gov ID: NCT05561998 . Registered in September 28, 2022.